Comparative analysis of the soil microbiome and carbohydrate content of Anthoxanthum nitens (Sweetgrass) and other Poaceae grass tissues and associated soils - King, Marissa L.; Bajwa, Barinder; Hanna, Naomi; Xing, Xiaohui; Low, Kristin E.; Neuberger, Patrick; Hall, Erin; Veltri, Michael; Weighill, Brett; Klassen, Leeann; Plain Eagle, Noreen; Big Bull, William; et al. (Frontiers in Microbiology, 2025)
Sweetgrass (Anthoxanthum nitens) is a culturally and environmentally significant perennial grass to many Indigenous Peoples; however, little is known about the potential of Sweetgrass as a contributor to soil health, biodiversity, and climate adaptation. Here, a team of transdisciplinary experts from academia, a non-governmental organization, and a First Nation community collaborated to investigate the structural composition of the rhizomes, stems, and leaves of greenhouse-grown Sweetgrass in comparison to other Poaceae grass members found in a nearby field. The data shows that the monosaccharide composition of A. nitens was evenly distributed throughout the three tissues, and that cellulose was the predominant polysaccharide followed by glucuronarabinoxylans. There were lesser amounts of xyloglucans, mixed-linkage glucans, homogalacturonans, and rhamnogalacturonans as the hemicellulosic and pectic polysaccharides, respectively. The carbohydrate composition seen in A. nitens was consistent with the other Poaceae grasses evaluated in this study, with the exception of Setaria chondrachne, which contained elevated pectin levels in its stems and leaves. Additionally, the analysis of the carbohydrate content within the soil samples revealed a higher abundance of carbohydrates within greenhouse soil when compared to field soil samples, with significantly more mannose, galactose, and galacturonic acid. Further, there were structural differences in the microbial communities across sampling sites, including a significant Unclassified / Non classifié increase in the abundance of Bacillus spp. in the greenhouse soil. Overall, this study provides the glycome and associated soil microbial community baseline for greenhouse-grown Sweetgrass.